Integrasi Sumberdaya Internal dan Orientasi Pasar sebagai Basis Strategi Bersaing pada Perusahaan Air Minum dalam Kemasan (AMDK) di Jawa Timur - -, Purwohandoko (Universitas Brawijaya, Indonesia, 2009)
The result of descriptive statistic analysis consistently shows that the higher the business scale the stronger the portfolios or Internal Resources owned, the better the implementation of market orientation, and the higher the company’s performance: but the competitive strategy selected and implemented by different companies vary, depending on their business scale. Big business scale tends to result in low cost leadership and smaller business scale tends to result in focus. However all business scales do not leave differentiation as a distinction and value for customer. The result of the hypothesis testing proved that after the integration of internal resources into market orientation as the basis of the selection and implementation of competitive strategy, it turned out that the influence of internal resources and market orientation toward company’s performance was not directly proved because it had been reduced after the existence of competitive strategy as an intervening variable, and there after 2 of the 7 hypothesis were not proved. Internal resources proved to influence market orientation, meaning that the internal resources strength supported the market orientation implementation. The models recommended were internal are integrative in nature and able to produce company performance through the appropriate implementation of competitive strategy. Internal resources and/or strong implementation of market orientation do not mean anything if they are transformed through appropriate implementation of competitive strategy. The loading result consistently indicated the reputation and organization of internal resources, cross function coordination on market orientation, learning and growth on company’s performance are the most dominant dimension implying the necessity of learning process in organization and resources management. Therefore the role of human resources as the key of sustainable competitive advantage needed to be managed through organization management system arrangement by establishing organization culture and collective awareness of the entire human resources of the company.Keywords: internal resources, competitive strategy